1990
DOI: 10.1089/jir.1990.10.637
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Various Cytokines on Interleukin-6 and Interferon-α Synthesis in Human Peripheral Blood Mononuclear Cells

Abstract: The effect of various recombinant cytokines on the induction of interleukin-6 (IL-6) synthesis induced in adherent and nonadherent cells of human peripheral blood mononuclear cells (PBMNC) by bacterial lipopolysaccharide (LPS) or concanavalin A (CA) was studied. The results showed that human interferon-(HuIFN)-alpha, -beta, and gamma at a concentration of 100-10,000 IU/ml enhanced the LPS-induced IL-6 production in the adherent cell fraction of PBMNC. However, in nonadherent cells, treatment with HuIFN-alpha o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
1
1

Year Published

1992
1992
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
2
1
1
1
Order By: Relevance
“…IFN-a injection resulted in the release of multiple pro-inflammatory factors (like IL-6 and IL-8) and of anti-inflammatory factors (IL-10) and the soluble TNF receptors p55 and p75. In line with our results are the (mainly in vitro) reports from Rosztoczy & Content, who demonstrated that IFN-a enhances lipopolysaccharide (LPS)-induced IL-6 production in the adherent cell fraction of human PBMC [27], and of Tilg et al, who showed that IFN-a induces the circulating TNF receptor p55 in healthy human volunteers [28]. Although Aman et al reported downregulation by IFN-a of IL-8 mRNA expression in patients with chronic myelogenous leukaemia [10], Ohashi et al reported IFN-a augmented IL-8 secretion from latently HIV-1-infected U937 cells [29].…”
Section: Discussionsupporting
confidence: 93%
“…IFN-a injection resulted in the release of multiple pro-inflammatory factors (like IL-6 and IL-8) and of anti-inflammatory factors (IL-10) and the soluble TNF receptors p55 and p75. In line with our results are the (mainly in vitro) reports from Rosztoczy & Content, who demonstrated that IFN-a enhances lipopolysaccharide (LPS)-induced IL-6 production in the adherent cell fraction of human PBMC [27], and of Tilg et al, who showed that IFN-a induces the circulating TNF receptor p55 in healthy human volunteers [28]. Although Aman et al reported downregulation by IFN-a of IL-8 mRNA expression in patients with chronic myelogenous leukaemia [10], Ohashi et al reported IFN-a augmented IL-8 secretion from latently HIV-1-infected U937 cells [29].…”
Section: Discussionsupporting
confidence: 93%
“…The effects of IL-2 on SVand HSV-1-induced IFN-a response appeared to be at least partially different in our experiments. IFN-g, and to a lesser extent IL-2, enhanced SV-induced IFN-a response in our studies whereas in those of Rostoczy and Content [22], IFN-g but not IL-2 could increase SV-induced IFN-a production. In their experiments, adherent cells were pretreated overnight with IL-2, whereas we induced PBMCs to produce IFN-a in the presence of IL-2, which may account for the differences in the results.…”
Section: Cytokines and Ifn-a In Hiv-1 Infection 439contrasting
confidence: 68%
“…It has been shown that it specifically promotes differentiation towards the type-1 immune response [19,20]. In addition, various cytokines enhance or down-regulate the virus-induced production of IFN-a in human blood leucocytes [21][22][23]. Together these data indicate that there may be an interaction between natural and adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that IFNγ enhances the amount of IL-6 secreted in response to LPS in various types of cells (231,232). Our study shows that IL-12 also increases the amount of IL-6 secreted by 4T1 TIMs in response to LPS in a manner that is independent of IFNγ.…”
Section: Il-12 Alters the 4t1 Tims Activation Of Mapk Pathway In Respsupporting
confidence: 59%